Development and evaluation of mucoadhesive bigel containing tenofovir and maraviroc for HIV prophylaxis - Margaret O. Ilomuanya; Ayotunde T. Hameedat; Edidiong N Akang; Sabdat O. Ekama; Boladale O. Silva; Alani S Akanmu (SpringerOpen, 2020)
Abstract Background Sexual transmission of HIV is the most common means of acquiring the disease. Topical microbicides have been investigated to prevent transmission. This study will use a specific entry inhibitor, maraviroc, and a nucleotide reverse transcriptase inhibitor (NRTI), tenofovir, a dual combination which will provide a synergist effect that can enhance the efficacy of HIV microbicides via a mucoadhesive dual compartment bigel. Bigel formulation via hydrogel organogel linkages were developed and evaluated for their physicochemical characteristics, safety, and anti-HIV efficacy. In vitro diffusion studies were performed with Franz diffusion cells having effective diffusion surface area of 1.76cm2 and receiver chamber volume of 15mL. Result The bigel formulations showed a viscosity ranging from 14179 to 14560 cPs and had a good spreadability and acidic pH in the range of 4.0 ± 0.34 to 5.2 ± 0.18. The bigel formulations showed good anti-HIV activity at a concentration of 0.1 μg/mL. The in vitro release study of maraviroc from the bigel formulations showed a release rate ranging from 2.675 to 3.838 μg/cm2/min½ while the release rate for tenofovir ranged from 3.475 to 3.825 μg/cm2/min½. The bigel formulations were non-toxic to the human vagina as there was < 1 log10 change in Lactobacilli crispatus viability. Conclusion This study successfully developed a dual compartment bigel containing maraviroc and tenofovir. BG C was found to be stable and safe towards vaginal and rectal epithelium, and it actively prevented HIV transmission. This bigel has the potential for long-term pre-exposure prophylaxis prevention of HIV transmission.